Economic Burden of Head Injury Patients Attending a Tertiary Level Hospital in a Developing Country Like Bangladesh (Bangladesh Journal of Neuroscience, 2014)
Objective: Objective of the study was to estimate the economic burden of head injury (HI) patients attending a tertiary level hospital. This study also tried to determine the socio-demographic characteristics, to estimate direct and indirect cost incurred by the head injury patients and to assess economic burden by different types of accidents causing head injury.Methods:The study was a cross-sectional descriptive study carried out to estimate the economic burden of head injury patients attending a tertiary level hospital during the period from January to June 2010, conducted at the neurosurgery department of Dhaka Medical College Hospital (DMCH). All the conscious head injury patients of both sexes, treated in Neurosurgery department of DMCH, willing to participate in the study were included in the study. Convenience type of non-probability sampling technique was followed and sample size of this study was 110. Face to face interview was conducted with the patient and / or attendant for data collection and specific pre-designed semi-structured and pre-tested questionnaire was used for the interview session. After Categorizing, coding, cleaning and summarizing, all data were analyzed by the software SPSS windows program version 12.0.Result: More than half (53.6%) of the patients of this study, were in younger age group (21 to 30 years) with mean (±SD) age of 29.1(±8.36) years. Majority of the patients (69.0%) were males, Average monthly family income of the patients was Tk.14,509.09 (±5762.49). Majority (36.4%) of the patients had primary level education while 20.9% were housewives. Major incidences of different types of accidents included road traffic accident (63.6%), assault (20.0%), industrial accident (8.0%) and fall from height (8.0%). Average length of the stay of the patients in the hospital was 7.43 (±3.64) days. In respect of direct cost, average travel cost incurred by the patients was Tk.3,628.18 (±2055.56), average drug cost was Tk.1,618 (±801.51), average laboratory investigation cost was Tk.2390 (±626.47) and average cost of food was Tk.2235.45 (±1208.19). Average direct treatment cost incurred by the patients was Tk.9590.10 (±4041.13). The average duration of absent from work place was 7.07 (±3.316) days and most of the patients average daily income (self) was Tk.340.65 (±158.97). Average loss of income due to illness was Tk.2415.32(±1623.68) and average cost behind giving tips to hospital staff by the patients was Tk.221.50 (±78.34). The average indirect cost of these study patients was Tk.2001.72 (±1869.27). Overall, average treatment cost incurred by the patients was Tk.12,008.05 (±5051.95). Majority (38.0%) had a cost from Tk10001 to Tk.15000.Conclusion: The study finding can help policy makers, public health specialists, future researchers and enthusiastic individuals to formulate specific strategies for reduction of economic burden of head injury patients by providing cost-effective health care services throughout the country.Bangladesh Journal of Neuroscience 2014; Vol. 30 (2): 104-111